Biodiversity of wild spice plants of the Central Kazakhstan region and their medicinal potential (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Pozdnyakova Y, Omarova G, Murzatayeva A, Tankibaeva N. 2022. Biodiversity of wild spice plants of the Central Kazakhstan region and their medicinal potential. Biodiversitas 23: 4609-4625. The Central Asian region stretches from the Caspian Sea in the west to the border of western China in the east. Central Kazakhstan occupies the space of steppe and semi-desert zones within the Turgay Plateau in the west and the Kazakh Uplands in the center and in the east. Due to the remoteness of the steppes of Central Kazakhstan from the oceans, the climate in the region is extremely continental and arid. Due to this, the diversity of plant species is quite small. In this work, we have studied the biodiversity of wild herbs growing in the climatic conditions of Central Asia. We also assessed the prospects of the found plant species as medicines. This study took place as part of the traditional summer practice of biology students in the period July-August 2019. The main method used in the field research was route reconnaissance. As a result of field research, 40 wild spice plant species belonging to 17 families were found. Among them, the most numerous are the families Lamiaceae - 9 species, Brassicaceae - 6 species, Apiaceae - 5 species, Asteraceae - 4 species, the families Rosaceae and Fabaceae - 2 species of herbs. All of these species are mentioned in a number of old recipes and can be revived and re-recommended for widespread use. A critical assessment of the literature on the medicinal properties of the studied spices irrefutably shows that they have enormous health potential. Based on the data obtained, it can be concluded that wild spice plants growing in the territory of Central Kazakhstan have a wide range of taste diversity and prospects for successful commercial exploitation.